EFFECTS OF PERCEIVED USEFULNESS, EASE OF USE, RISKS, AND INFORMATION QUALITY OF SALES PRODUCTIVITY APPS ON DSA’S BEHAVIOR - Kurniasari, Florentina; Gunardi, Ardi (Jurnal Riset Bisnis dan Manajemen, 2023)
Technological advancements have brought innovation in the financial industry with various platforms. Although these platforms are easily accessible, some Indonesians are still reluctant to use them, hence the need for proper introduction and information delivery. Peer-to-peer (P2P) lending platforms need to develop and implement applications that can monitor the activities and increase the productivity of direct sales agents (DSAs) to gain the trust of potential borrowers. This study analyses the influence of perceived usefulness, ease of use, risk, and information quality on the actual behaviour of DSAs when using sales productivity applications with behavioural intention as an intervening variable to be statistically processed using the Structural Equation Method. The questionnaire was distributed to DSAs of Modalku platform. The results showed that DSA's actual behaviour in using the application was significantly influenced by intention to use, perceived usefulness, ease of use, risk, and information quality. Perceived risk has the highest influence.